1995
DOI: 10.1159/000126856
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y: Distribution of Immunoreactivity and Quantitative Analysis in Diencephalic Structures and Cerebral Cortex of Dwarf Hamsters under Different Photoperiods

Abstract: The distribution of neuropeptide Y-like immunoreactivity (NPY-LI) was investigated by immunohistochemistry and radioimmunoassay (RIA) in the brain of the Djungarian hamster (Phodopus sungorus) held under either long or short photoperiods. In the diencephalic and telencephalic structures studied, distinct patterns of NPY-LI were basically consistent in male and female animals of both groups. NPY levels detected by RIA from tissue samples taken at six time points throughout the 24-hour cycle were in the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…A candidate site is the habenular region, to which the pineal is thought to be connected via its stalk (see below). NPY fibres have been indeed found in the pineal stalk of rat and cow (Reuss and Moore 1989;Phansuwan-Pujito et al 1993) and a relatively dense NPY-immunoreactive fibre plexus has been seen in the habenular nuclei of the ground squirrel and hamster (Reuss et al 1990a;Reuss and Olcese 1995). The persistence of fibres in the pineal upon SCGX has also been reported in other studies in which, for example, presumed serotonergic fibres have been found in dog .…”
Section: Extrasympathetic Innervation Of the Pineal Glandsupporting
confidence: 62%
See 2 more Smart Citations
“…A candidate site is the habenular region, to which the pineal is thought to be connected via its stalk (see below). NPY fibres have been indeed found in the pineal stalk of rat and cow (Reuss and Moore 1989;Phansuwan-Pujito et al 1993) and a relatively dense NPY-immunoreactive fibre plexus has been seen in the habenular nuclei of the ground squirrel and hamster (Reuss et al 1990a;Reuss and Olcese 1995). The persistence of fibres in the pineal upon SCGX has also been reported in other studies in which, for example, presumed serotonergic fibres have been found in dog .…”
Section: Extrasympathetic Innervation Of the Pineal Glandsupporting
confidence: 62%
“…A radioimmunological determination has shown high NPY concentrations in the pineal of rat (Chronwall et al 1985;Olcese 1994) and hamster (Reuss and Olcese 1995). In the latter, the amount decreases at the light-dark transition (Reuss and Olcese 1995).…”
Section: Sympathetic Trunk Cervical Ganglia and Sympathetic Innervatmentioning
confidence: 99%
See 1 more Smart Citation
“…It binds to receptors located in various brain nuclei involved in feeding regulation, notably the ARC, and it regulates food intake in various mammalian species (Lotter et al, 1981;Danguir, 1988;Fehlmann et al, 2000;Stengel et al, 2010Stengel et al, , 2015. Interestingly, independent studies have reported that Kp (Revel et al, 2006a;Smith et al, 2008), RFRP-3 (Revel et al, 2008;Smith et al, 2008), NPY (Lakhdar-Ghazal et al, 1995Reuss and Olcese, 1995;Skinner and Herbison, 1997), b-endorphin (Roberts et al, 1985;Ebling and Lincoln, 1987), and somatostatin (Webb et al, 1985;Herwig et al, 2012;Klosen et al, 2013;Dumbell et al, 2015) display significant variations in the brain of different mammalian species placed in artificial long or short photoperiods.…”
mentioning
confidence: 99%
“…Among neurotransmitters occurring in the pineal nerve endings, norepinephrine (NE) and neuropeptide Y (NPY) are present in the highest amounts (Williams et al 1989, Møller 1990, Møller et al 1990, 1996, Zhang et al 1991, Cozzi et al 1992, Olcese 1994, Reuss and Olcese 1995, Drijfhout et al 1996a, Mikkelsen and Møller 1999, Simonneaux and Ribelayga 2003. Both substances co-exist in the sympathetic nerve fibers, but NPY also occurs in a small population of non-sympathetic fibers, probably of the central origin , Zhang et al 1991, Møller et al, 1996, Møller 1999.…”
Section: Introductionmentioning
confidence: 99%